Palladium-Catalyzed Amination of Aryl Sulfides and Sulfoxides with Azaarylamines of Poor Nucleophilicity - Pratap, Ramendra; Yorimitsu, Hideki (Synthesis, 2019)
The amination of aryl sulfides and sulfoxides with azaarylamines is investigated using a palladium-N-heterocyclic carbene (NHC) complex. Because azaarylamines are less nucleophilic than anilines, more reactive diaryl sulfides and sulfoxides are found to be suitable coupling partners that liberate better leaving arenethiolate or arenesulfenate anions, instead of aryl methyl sulfides as reported previously.
Keywords: amination; palladium; cross-coupling; organosulfur compounds